Outcomes and Prognostic Factors of Pulmonary Hypertension Patients Undergoing Emergent Endotracheal Intubation. (March 2023) - Hong, Andrew W.; Toppen, William; Lee, Joyce; Wilhalme, Holly; Saggar, Rajan; Barjaktarevic, Igor Z.
Background: Emergent endotracheal intubations (ETI) in pulmonary hypertension (PH) patients are associated with increased mortality. Post-intubation interventions that could increase survivability in this population have not been explored. We evaluate early clinical characteristics and complications following emergent endotracheal intubation and seek predictors of adverse outcomes during this post-intubation period.Methods: Retrospective cohort analysis of adult patients with groups 1 and 3 PH who underwent emergent intubation between 2005-2021 in medical and liver transplant ICUs at a tertiary medical center. PH patients were compared to non-PH patients, matched by Charlson Comorbidity Index. Primary outcomes were 24-h post-intubation and inpatient mortalities. Various 24-h post-intubation secondary outcomes were compared between PH and control cohorts.Results: We identified 48 PH and 110 non-PH patients. Pulmonary hypertension was not associated with increased 24-h mortality (OR 1.32, 95%CI 0.35-4.94, P = .18), but was associated with inpatient mortality (OR 4.03, 95%CI 1.29-12.5, P = .016) after intubation. Within 24 h post-intubation, PH patients experienced more frequent acute kidney injury (43.5% vs. 19.8%, P = .006) and required higher norepinephrine dosing equivalents (6.90 [0.13-10.6] mcg/kg/min, vs. 0.20 [0.10-2.03] mcg/kg/min, P = .037). Additionally, the median P/F ratio (PaO2 /FiO2 ) was lower in PH patients (96.3 [58.9-201] vs. 233 [146-346] in non-PH, P = .001). Finally, a post-intubation increase in PaCO2 was associated with mortality in the PH cohort (post-intubation change in PaCO2 +5.14 ± 16.1 in non-survivors vs. −18.7 ± 28.0 in survivors, P = .007).Conclusions: Pulmonary hypertension was associated with worse outcomes after emergent endotracheal intubation than similar patients without PH. More importantly, our data suggest that the first 24 hours following intubation in the PH group represent a particularly vulnerable period that may determine long-term outcomes. Early post-intubation interventions may be key to improving survival in this population.